Perlindungan Hukum Kohabitasi Hak Atas Privasi Terhadap Pengaturan Pidana Berdasarkan Perspektif HAM - Pribadi, Muhammad Teguh; Simangunsong, Frans (Media Hukum Indonesia (MHI), 2026)
This study examines legal protection for cohabitation in relation to the right to privacy and criminal regulation from a human rights perspective. Cohabitation is understood as a life choice between two adults in the most private sphere and should be protected from state intervention. However, Article 412 of the Criminal Code opens the possibility of the use of criminal law that could potentially violate human dignity through actions such as raids or inspections of domestic spaces. This study uses a normative juridical method by analyzing the 1945 Constitution, the Human Rights Law, the Criminal Code, the ICCPR, the Universal Declaration of Human Rights, and General Comment No. 16 to assess the compatibility of criminal regulations with the principles of privacy, personal autonomy, and limitations on state power. The study results indicate that the criminalization of cohabitation does not meet the parameters of legality, necessity, and proportionality because it is a victimless act that does not cause concrete harm and has the potential to create discrimination against women and vulnerable groups. The complaint mechanism also does not adequately protect the right to privacy because it leaves room for families to determine whether the state can intrude into an individual's private sphere. This study emphasizes the need for an evaluation of Article 412 of the Criminal Code through judicial review to align criminal policy with human rights principles and constitutional guarantees..